The slave trade the story of the Atlantic slave trade ; 1440 - 1870 - Thomas, Hugh 1931-2017 (Simon & Schuster, 1997)
Chronicles the history of the African slave trade by Portugal, Brazil, Great Britain, France, Spain, the Netherlands, and the United States, from the first Portuguese slaving expeditions, through the abolitionist movements, to the final days of the trade in Cuba and Brazil. Includes who the slavers and abolitionists were, how profitable the business was, the African rulers and peoples who collaborated, the towns which grew rich on the trade, and more.
Keywords: Geschichte 1440-1870; Esclaves - Commerce - Histoire; Slavenhandel; Geschichte; Slave trade -- History; Sklavenhandel; Atlantischer Raum